Comparação entre a imagem radiografica interproximal convencional e a digital direta na detecção de cáries proximais - Araujo, Elaine Aparecida Félix de [UNESP] (2001)
The purpose this study was to evaluate the accuracy of proximal caries detectíon comparing enhanced and unenhanced Sidexis CCD-based digital image with Ektaspeed Plus and lnsight films. Fifty-two extracted teeth posterior were imaged under identical standardized geometric and exposure condítions. Four observes, using six point confidence scale, rated 104 proximal surfaces for the presence or absence of carious lesions by means of four image modalities: a) Ektaspeed Plus films; b) INSIGHT films; c) unenhanced Sidexis displays; d) obsever enhanced. The real pattern was determined by microscopy analysis of sections. Receiver Operating Characteristic curves were generated analyzed with Kappa the according interobservers. The results indicated that there wasn't significant difference between unenhanced Sidexis and film images (P >0,05)